A Strategy Business Development Strategy Trough The Canvas Model Artwork House AL-FALAH Ploso Mojo - Alifiyah, Nur (Mabny: Journal of Sharia Management and Business, 2022)
Abstract : The activities of the corporate officers at the Al Falah Ploso Mojo Foundation are one of the economic independence programs of the Indonesian bankers given to enhance the economic independence program of the financial sector and create the interests of the business wizard for the young. In addition, this research aims to increase the productivity of the business in order to be more developed and able to compete in the market. To develop the handicraft business, the manager of the Al Falah Ploso Mojo Home Business Unit needs to improve its business strategy in order to increase sales and revenue. Efforts to improve the quality of business strategy are made by analyzing nine key elements of the Canvas model business and thoroughly analyzing them using SWOT analysis for power tests,weaknesses,threats and opportunity. This research is a qualitative research that is described and produces four managerial implications that require a business strategy improvement.. Keywords: Business Model Canvas, SWOT analysis, Islamic boarding school economic independence, Managemen Strategi, Business Develoment strategy